2020
DOI: 10.1037/pspa0000196
|View full text |Cite
|
Sign up to set email alerts
|

Front in the mouth, front in the word: The driving mechanisms of the in-out effect.

Abstract: Words for which the consonantal articulation spots wander from the front to the back of the mouth (inward) elicit more positive attitudes than words with the reversed order (outward).The present paper questions the common theoretical explanation of this effect, namely an association between articulation movements and oral movements during ingestion and expectoration (inward resembles eating which is positive; outward resembles spitting which is negative). In four experiments (total N = 468), we consistently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 74 publications
3
57
1
Order By: Relevance
“…Very recently, Körner, Bakhtiari and Topolinski (2019), suggested the role of motor fluency in shaping the in–out effect and demonstrated that training outward articulation sequences could block or even invert the established preference for inward wandering ones (see Godinho & Garrido, 2019 and also Maschmann, Körner, Boecker, & Topolinski, 2020 for an overview of the state of the art). Independently of the debate surrounding the origin of the effect, these findings demonstrate that the in–out effect is permeable to fluency manipulations.…”
Section: Relevant (Marketing‐wise) Boundary Conditionsmentioning
confidence: 99%
“…Very recently, Körner, Bakhtiari and Topolinski (2019), suggested the role of motor fluency in shaping the in–out effect and demonstrated that training outward articulation sequences could block or even invert the established preference for inward wandering ones (see Godinho & Garrido, 2019 and also Maschmann, Körner, Boecker, & Topolinski, 2020 for an overview of the state of the art). Independently of the debate surrounding the origin of the effect, these findings demonstrate that the in–out effect is permeable to fluency manipulations.…”
Section: Relevant (Marketing‐wise) Boundary Conditionsmentioning
confidence: 99%
“…This stream of research also shows that since bilabials are associated with innocence and children, when creating names for villains, respondents tend to avoid using bilabials (Kawahara, 2019). Such examples and prior research suggest a link between early communication (e.g., bilabials, front consonants which appear early in life) with concepts (e.g., pleasantness, likability) (Maschmann et al, 2020). Similarly, languages have developed from both manual and lip gestures-the earliest forms of communication.…”
Section: Discussionmentioning
confidence: 74%
“…vomiting) was originally proposed as the mechanism behind the in/out effect, recent evidence suggests alternative explanations (e.g. pronounceability, fluency, greater preference for first consonants) (Maschmann et al, 2020;Topolinski et al 2014). For example, one alternative explanation is that in natural languages, words with sounds originating from the front of the mouth (e.g., /m/) are more abundant than words with sounds originating from the back of the mouth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations